Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-05-17T16:35:53+02:00

7x + 4y = -5x + 3y = 9

donc 7x + 5x + 4y -3y -9 = 0

ou 12x +y -9 = 0

2x + 3y = 30x - y = 5

donc 30x - 2x - y - 3y - 5 = 0

ou 28x - 3y - 5 = 0

Donc on a le système

12x + y - 9 = 0

28x - 3y - 5 = 0

Dans la première équation:

12x + y -9 = 0

donc y = -12x +9

Donc en remplaçant y dans la deuxième équation on obtient :

28 x - 3 * ( -12x + 9 ) - 5 = 0

ou 28x + 36x - 27 - 5 = 0

ou 64 x -32 = 0

64x =32

x = 32/64 = 0,5

Donc y = -12 * 0,5 + 9 = -6 + 9 = 3